Efektivitas Layanan Weekend Banking (Studi BMI KCP PIM ) . - Farhah, Rifa (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
The Effectiveness of Weekend Banking Services (Study at BMI KCP PIM). The aim of this research is to analyze the effectiveness of weekend banking services at Bank Muamalat Indonesia. The method that used in this research is linier regression and. The result shown that the value of adjusted R-squared was 0.313409. It means that customer’s preference (dependent variable) was influenced by location, brand image, and, product and services in the amount of 31.34% and the others 68.66% was influenced by the others factor. From the paired sample t-test shown that the weekend banking services still not effective to increase the third party funds  DOI:10.15408/aiq.v6i1.1370